Price Parity of Reconstructing Technological Supply Chain Capacity in the Agricultural Sector of Ukraine - O. Varchenko; I. Svynous; V. Skotsyk; Y. Grynchuk; L. Khakhula; Larysa Khakhula (International Journal of Supply Chain Management, 2018)
Abstract- The main form of equivalence of professional trade in the agricultural sector remains the parity of agricultural producers and the prices of goods and services of industrial origin that they buy. The price of equality for the supply chain capacity of agricultural products is equal to the product of the price level for the base period and the industrial product price index for the current year. The efficient functioning of agriculture depends on the equivalence of relations with other sectors of the national economy, mainly with industry, as a supplier of material and technical resources. The main reason for the appearance of price disparity is a significant reduction in the production of agricultural machinery by agricultural machinery companies compared to the pre-reform period. Now in economic theory two methodical approaches are used to calculate the index of equality between agriculture. The price of equality for the supply chain capacity of agricultural products is equal to the product of the price level for the reference period and the index of prices produced in current year products and input resources. The first (concept of income) presupposes that the price ratio between agricultural and industrial products must influence the evolution of production volumes. The calculation of the parity index using the concept of exchange provides for the determination of the correlation of the price indices for agriculture. The price of equality for the capacity of the agricultural technology supply chain is equal to the product of the price level for the base period and the price index of industrial products in agricultural products and machinery of the current year. This approach truly reflects the role of agriculture in the system of market-money relations. .Keywords- price parity, technological supply chain capacity, parity index, agricultural products, modernization